If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 9) + -15 = -3 Reorder the terms: 2(9 + x) + -15 = -3 (9 * 2 + x * 2) + -15 = -3 (18 + 2x) + -15 = -3 Reorder the terms: 18 + -15 + 2x = -3 Combine like terms: 18 + -15 = 3 3 + 2x = -3 Solving 3 + 2x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = -3 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = -3 + -3 2x = -3 + -3 Combine like terms: -3 + -3 = -6 2x = -6 Divide each side by '2'. x = -3 Simplifying x = -3
| -3(m-6)=18 | | 3*12+4=n | | -4(m-8)-7m=-4(1+2m) | | -3/17p=-8 | | 12-3/2y=14 | | n-2=-4 | | 1.50p/10= | | 2(4w-5+w)=90 | | -5x+3(-4x-11)=137 | | 2x+6+4x-3= | | Log[5]x^2=log[5]16 | | (4.5)18(x)=126 | | (H+6)(h-2)h=672 | | 0.6x+1.18=0.8x+6.18 | | -28=3x | | (4.5)18x=126 | | 132/11=n | | 0.25w+0.17f=80000 | | (4.5)(18)x=126 | | 11x+12y-10=0 | | 2ln(x+7)=2.7 | | 7x+5+5x= | | -7=1+2 | | 4.5*18x=126 | | -7x-8x=-15 | | t/2-1=0 | | b^3*b^2=0 | | 4/7t-1/14t=t-9/2 | | (W+40)w=6000 | | .6612+4x+4x^2=0 | | 3+3s-(4s+1)-(2s+6)= | | -8y-1=-7y-6 |